Psychometric Analysis of the Self-Efficacy Inventory for Multiple Intelligences-Revised (SIMI-R) in Peruvian High School Students - Aliaga Tovar, Jaime (2018)
The objective of this instrumental study (Ato, López & Benavente, 2013) or psychometric-type (Alarcón, 2008) was to estimate the validity and reliability of the Self-Efficacy Inventory for Multiple Intelligences-Revised (IAMI-R, Pérez & Cupani, 2008) in Peruvian students of fifth year of high school. We worked with a sample of 1304 adolescents, with an average age of 16.81, divided into two groups of 652. Reliability was calculated with the Ordinal Alpha (Contreras & Novoa-Muñoz, 2018) and with the McDonald’s Omega coefficient, obtaining appropriate values. The Exploratory Factor Analysis (AFE) confirms the eight factors of the original version that explain 70% of the variability of the scores. With the confirmatory factorial analysis (CFA), adjustment indices were obtained confirming this factorial structure: SSc2 = 1857.73, gl = 1047, SSc2 / gl = 1.77, RMSEA = .035, SRMR = .049, CFI = .915, and TLI = .908. The results confirm that the IAMI-R is adequate to evaluate self-efficacy associated with multiple intelligences in Peruvian students who complete high school.